CONTRIBUTION OF DNA REPAIR ENZYMES GENES POLYMORPHISM TO CHROMOSOMAL MUTAGENESIS IN HUMAN LYMPHOCYTES (REVIEW) - V. I. Minina (Вестник Кемеровского государственного университета, 2013)
A review of scientific publications on the analysis of the correlation between chromosome aberrations and DNA repair enzymes genes polymorphism in healthy individuals and cancer patients is provided. The paper presents prospects of using SNP in the DNA repair enzymes genes as markers of increased sensitivity to clastogenes. The importance of such studies for the residents of the industrial region is proved.